2015
DOI: 10.3109/08916934.2015.1058370
|View full text |Cite
|
Sign up to set email alerts
|

PDCD1single nucleotide genes polymorphisms confer susceptibility to juvenile-onset systemic lupus erythematosus

Abstract: Juvenile-onset systemic lupus erythematosus (JSLE) is a multisystem autoimmune disease in which both the genetic and environmental factors seem to be involved in the etiopathogenesis of the disease. The aim of this study was to evaluate the association of programmed cell death 1 (PDCD1, also called PD-1) gene polymorphisms with JSLE susceptibility in Iranian population. In this case-control association study, three PDCD1 SNPs, including PD-1.1 G/A, PD-1.3 G/A and PD-1.9 C/T were genotyped in 50 Iranian patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 26 publications
(51 reference statements)
0
13
0
1
Order By: Relevance
“…[1116]. Interestingly, accumulating evidences showed that PD-1 single nucleotide polymorphisms (SNPs) were also correlated with susceptibility to human malignancy (e.g., thyroid cancer, breast cancer, cervical cancer, non-small cell lung cancer and gastric cancer et al .)…”
Section: Introductionmentioning
confidence: 99%
“…[1116]. Interestingly, accumulating evidences showed that PD-1 single nucleotide polymorphisms (SNPs) were also correlated with susceptibility to human malignancy (e.g., thyroid cancer, breast cancer, cervical cancer, non-small cell lung cancer and gastric cancer et al .)…”
Section: Introductionmentioning
confidence: 99%
“…Association of polymorphisms in programmed cell death 1 (PDCD1) 20,21 , protein tyrosine phosphatase non-receptor type 22 (PTPN22) 22,23 , and IL-4 24 genes, as well as C1q rs292001 SNP 25 has been observed in JSLE patients. In our previous study, we evaluated the association of programmed cell death1( also called PD-1) gene polymorphisms with JSLE susceptibility in the Iranian population and our finding supported the influence of the PD1.1 SNP on the development of juvenile systemic lupus erythematosus (JSLE) in the Iranian population 21,26 .…”
Section: Alleles and Genotypes Frequenciesmentioning
confidence: 99%
“…Recently, a number of case-control studies have investigated the relationship of PDCD1 polymorphisms with the susceptibility of SLE, but the results were inconsistent [1014]. Prokunina et al .…”
Section: Introductionmentioning
confidence: 99%
“…But Mahmoudi et al . [14] found that PD1.1 polymorphism played a key role in the juvenile-onset SLE development in Iranian population. Based on these findings, the effects of PDCD1 polymorphisms have been widely discussed, but no conclusive relationships have been determined.…”
Section: Introductionmentioning
confidence: 99%